Analisis Metode Outing Class terhadap Kemampuan Menulis Siswa pada Pembelajaran Bahasa Indonesia Kelas III SDN 2 Baregbeg - Kurniasih, Kurniasih; Febriyani, Shoimatun; Azizah, Amalia Nurul (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the application of the outing class method on students' writing skills in Indonesian language learning in grade III of SDN 2 Baregbeg. The study used a qualitative approach with a case study method. The research subjects consisted of 22 third-grade students. Data were collected through observation, interviews, and documentation, then analyzed descriptively and qualitatively with an emphasis on the process and results of students' writing after participating in the outing class activity. The results of the study show that the application of the outing class method was carried out in three stages, namely planning, implementation, and follow-up. In the planning stage, the teacher prepared the objectives, location, and observation sheets. In the implementation stage, students were invited to observe the school environment, record their observations, and discuss them in groups. In the follow-up stage, students wrote about their experiences in the form of simple essays. The results of the students' writing showed improvement in terms of the relevance of the content to the theme, clarity of the main ideas, paragraph structure, vocabulary usage, language rules, and creativity. The conclusion of this study shows that the outing class method has a positive impact on improving students' writing skills, both in terms of content, structure, and learning motivation.